2017
DOI: 10.1103/physreve.96.042131
|View full text |Cite
|
Sign up to set email alerts
|

Finite-size effects in canonical and grand-canonical quantum Monte Carlo simulations for fermions

Abstract: We introduce a quantum Monte Carlo method at finite temperature for interacting fermionic models in the canonical ensemble, where the conservation of the particle number is enforced. Although general thermodynamic arguments ensure the equivalence of the canonical and the grand-canonical ensembles in the thermodynamic limit, their approach to the infinite-volume limit is distinctively different. Observables computed in the canonical ensemble generically display a finite-size correction proportional to the inver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Thus this method is particularly appealing within QMC and, quite recently, is becoming widely used for the study of strongly corre-lated systems. On the other hand, in a recent work [31], by using finite-temperature determinant quantum Monte Carlo without TABCs, the convergence of physical quantities to the thermodynamic limit have been examined for the canonical ensemble (CE) and the grand-canonical ensemble (GCE). It has been shown that GCE provides a convergence faster than CE.…”
Section: Introductionmentioning
confidence: 99%
“…Thus this method is particularly appealing within QMC and, quite recently, is becoming widely used for the study of strongly corre-lated systems. On the other hand, in a recent work [31], by using finite-temperature determinant quantum Monte Carlo without TABCs, the convergence of physical quantities to the thermodynamic limit have been examined for the canonical ensemble (CE) and the grand-canonical ensemble (GCE). It has been shown that GCE provides a convergence faster than CE.…”
Section: Introductionmentioning
confidence: 99%
“…The charge gap ∆ C and the spin gap ∆ S , with ∆ C > ∆ S , are monotonically increasing with t ⊥ and U . Gapped systems exhibit, as a function of the linear size, a fast approach to the thermodynamic limit [44,45]. Figure 2 illustrates the temperature dependence of the nearest-neighbor hopping term t i,i+1 inĤ E for t ⊥ = 2 and 2.5 and fixed coupling constants t = 1 and U = 4.…”
mentioning
confidence: 99%
“…[22] for more details on the formulation. A similar technique can be used to simulate the canonical ensemble [34]. Simulations have been performed using the ALF package [35].…”
Section: Methodsmentioning
confidence: 99%